Exercise and motivational text messaging to support physical activity behaviour change in a population with obstructive sleep apnoea: a feasibility study - Margot Skinner; Ben Brockway; Debra Waters; Sarah Rhodes (CSIRO Publishing, 2022)
Introduction Patients with obstructive sleep apnoea (OSA) commonly present in primary care. Increasing physical activity reduces symptoms and severity of OSA. Low motivation is a barrier to physical activity in adults with OSA. Aim To investigate the feasibility and acceptability of an exercise and personalised text messaging programme to enhance motivation and support physical activity behaviour change in adults with OSA. Methods Participants were recruited from the local Sleep Clinic. Exclusion criteria were unstable angina, and/or poorly controlled hypertension. The intervention comprised three groups, who received either individual exercise prescription, personalised text messages or both over a 24-week period. Participants were allocated to one of the three groups. The primary outcome was feasibility of study design including participant recruitment and retention. Secondary outcomes were a change in 6-min walk distance and exercise self-efficacy over time. Results Thirty participants were recruited, 17 male and 13 female, with a mean age of 54.6 years. The study design appears feasible and the outcome measures used were acceptable to participants. Recruitment and retention rates were lower than anticipated. A trend towards increased functional exercise capacity was identified in all three groups, along with a corresponding increase in exercise self-efficacy over time. Discussion Exercise and personalised text messaging both appear to offer an acceptable and feasible means to increase physical activity in adults with OSA. A larger scale trial may provide justification for physiotherapist input to support patients with OSA to address physical inactivity.